AN OVERVIEW OF MOST USED FOREIGN DIRECT INVESTMENT THEORIES - oppong, clement (Archives of Business Research, 2018)
Due to the importance attached to the flow of Foreign Direct Investment (FDI) as its roles toward global integration cannot be neglected, different theories have been forwarded to explain the reasons and movement of foreign capital across borders. Despite the existence of numerous FDI theories, there is no single theory which could serve as “one in all” theory, therefore this paper was theoretically purported to unveil those theories that are most always used to explain the movement of foreign direct investment.